Confirmation that eagle fatalities can be reduced by automated curtailment of wind turbines. Issue 3 (26th August 2022) - McClure, Christopher J. W.; Rolek, Brian W.; Dunn, Leah; McCabe, Jennifer D.; Martinson, Luke; Katzner, Todd E.
Abstract: Automated curtailment is potentially a powerful technique to reduce collision mortality of wildlife with wind turbines. Previously, we used a before–after–control–impact framework to demonstrate that eagle fatalities declined after automated curtailment was implemented with the IdentiFlight system at a wind power facility in Wyoming, USA. We received substantial interest and feedback regarding our study and, here, we implement several analytical suggestions and include more recent data that strengthen the inference we draw from our results. The five main analytical suggestions we received were to (1) exclude from analysis data that were collected during the period when automated curtailment was only partially implemented; (2) only analyse data from a single make and model of turbine; (3) evaluate changes in the rate of fatality, instead of the yearly numbers of fatalities that result from fluctuations around that rate; (4) calculate a standard measure determining effects of a treatment in a before–after–control–impact study and (5) examine yearly fluctuations of the fatality rate during the before period. After incorporating these suggestions and including additional data collected since the prior paper was published, our results confirm prior work. We demonstrate that eagle fatalities were reduced by 85% (95% highest density interval = 12%, 100%) after implementation of automated curtailment. Rate of fatalities declined by 2.85 eagles per year (−0.67, 5.70) between before and after periods at the treatment site and increased by 2.26 eagles per year (−1.77, 7.37) at the control site. Overall, the fatality rate declined by 4.91 (−0.27, 11.27) more eagles per year at the treatment site than at the control site. The probability that the fatality rate declined at the treatment site relative to the control site was 0.97. Our re‐analysis strengthens our inference by using more robust analyses and data to support the conclusions of the prior study suggesting that automated curtailment was effective at reducing eagle fatalities at our treatment site. Because of the site‐ and species‐specific nature of our work, future research should examine the efficacy of automated curtailment at other sites, with other species, and under different curtailment regimes. Abstract : Previously, we used a before‐after‐control‐impact framework to demonstrate that eagle fatalities declined after automated curtailment was implemented with the IdentiFlight system at a wind power facility in Wyoming, USA. We received substantial interest and feedback regarding our study and, here, we implement several analytical suggestions and include more recent data that strengthen the inference we draw from our results. Our re‐analysis strengthens our inference by using more robust analyses and data to support the conclusions of the prior study suggesting that automated curtailment was effective at reducing eagle fatalities at our treatment site.